Growth and equity a critique of the Lewis-Kuznets tradition with special reference to India - Datta, Anindya (Calcutta Oxford University Press, 1986)
Critique of the theories of William Arthur Lewis, b. 1915 and Simon Smith Kuznets, b. 1901, development economists.
Bibliography: p. [105]-115.
Includes index.
Keywords: Kuznets, Simon Smith -- 1901-.; Lewis, W. Arthur (William Arthur) -- 1915-.; Economic development; India -- Economic conditions -- 1947-.